The description of five new species of the genus Pantolyta (Hymenoptera, Diapriidae) from Africa - Chemyreva, Vasilisa G.; Kolyada, Victor A. (Zootaxa, 2023)
The genus Pantolyta is recorded for the first time from Africa. Five new species: Pantolyta gabonica sp.n., P. mostovskii sp.n., P. natalensis sp.n., P. noorti sp.n., and P. platycephala sp.n. are described from South Africa and Gabon. All species are keyed and illustrated.